2018
DOI: 10.21833/ijaas.2018.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of groundwater rising due to rainfall at far field in triggering landslide

Abstract: Landslide is a major issue in tropical countries. The intensive rainfall is the main triggering factor for a landslide that causes a loss in lives and properties. Landslide's triggering factors are several such as rain infiltration, earthquake, and human activities and so on. Those factors are very common. In this paper, the effect of rising of groundwater table in triggering landslide with respect to soil type, soil permeability and rain intensity in a regional scale were studied by running coupled seepage-sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The study projected area wise annual usable and potential recharge between 183 to 1287 mm and 135 to 1910 mm, respectively. The approximations of net recharge in Bangladesh have increased from 132 mm/yr over a period from 1975 to 1980 to about 190 mm/yr for the period of 2002 to 2007 [47]. Recent past studies confirmed that the ratio of groundwater recharge and abstraction in the country gradually downfall.…”
Section: Study Area-geomorphology Hydrology and Water Type 21 Geomorphologymentioning
confidence: 97%
See 1 more Smart Citation
“…The study projected area wise annual usable and potential recharge between 183 to 1287 mm and 135 to 1910 mm, respectively. The approximations of net recharge in Bangladesh have increased from 132 mm/yr over a period from 1975 to 1980 to about 190 mm/yr for the period of 2002 to 2007 [47]. Recent past studies confirmed that the ratio of groundwater recharge and abstraction in the country gradually downfall.…”
Section: Study Area-geomorphology Hydrology and Water Type 21 Geomorphologymentioning
confidence: 97%
“…Rain and floodwater are the principal sources of groundwater recharge in Bangladesh. Numbers of studies forecast that vast groundwater-fed irrigation would prolong net recharge in areas where soil properties and surface lithology are good permeable that favor recharge [6], [46], [47]. The study projected area wise annual usable and potential recharge between 183 to 1287 mm and 135 to 1910 mm, respectively.…”
Section: Study Area-geomorphology Hydrology and Water Type 21 Geomorphologymentioning
confidence: 99%
“…The applied rainfall intensity, which was a moderate magnitude, was selected as 25 mm/hr (0.6 m/day). This value was chosen based on prior research studies that have documented rainfall intensities ranging from 10 mm/hr to 200 mm/hr [16], [17], [18].…”
Section: Boundary Conditionsmentioning
confidence: 99%